Preparation method and application of magnetic polymer microspheres
Magnetic polymer microspheres were prepared by three-step method, which solved the problems of complex preparation methods, harsh conditions and unstable performance in the prior art, and achieved the effects of narrow particle size distribution, adjustable magnetic response and strong protein adsorption ability.
Patent Information
- Application Number
- CN202311164354.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-11
- Publication Date
- 2025-03-11
AI Technical Summary
The preparation method of magnetic polymer microspheres in the prior art has problems such as harsh synthetic conditions, high equipment requirements and complex process, resulting in wide particle size distribution, unstable magnetic response and insufficient protein adsorption capacity.
Magnetic polymer microspheres are prepared by a three-step method. First, polymer-based spheres are formed through polymerization reaction, then magnetic particles are deposited on their surface and the polymer layer is coated. Finally, an outer polymer layer is formed through polymerization reaction to ensure that the magnetic particles are sealed.
It has achieved a narrow particle size distribution, tunable magnetic response and good protein adsorption ability, which is suitable for protein isolation, purification or coupling.
Smart Images

Figure CN119591908A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnetic materials, and in particular relates to a preparation method of magnetic polymer microspheres and applications thereof. Background Art
[0002] Magnetic nanoparticles have unique physical properties such as superparamagnetic properties, high coercivity, low Curie temperature and high magnetic susceptibility, which have attracted people's attention in magnetic imaging, nanoprobes, biomedicine, drug delivery, tumor therapy, catalysis and magnetic separation. The composition of magnetic nanoparticles includes Fe, Co, Ni and their derivatives. Iron oxide nanoparticles have attracted more attention due to their easy synthesis, adjustable size and structure, good biocompatibility and effectiveness of surface modification.
[0003] Methods for synthesizing magnetic nanoparticles include coprecipitation, hydrothermal, solvothermal, sol-gel, microemulsion template, and high-temperature decomposition. These methods have been widely studied and discussed in many literatures and patents for synthesizing magnetic particles of different crystal forms, morphologies, and particle sizes. However, the magnetic nanoparticles synthesized by these methods have some disadvantages in certain applications: (1) The particle size is small, in the range of several hundred nanometers, which is not conducive to the capture or separation of larger targets; (2) The magnetic nanoparticles have poor stability and are easily oxidized, resulting in possible changes in physical properties; (3) They have high surface energy, are prone to aggregation or agglomeration, and are difficult to disperse. In order to circumvent the above defects in applications, magnetic nanoparticles can be combined with polymer microspheres to form magnetic polymer microspheres. Magnetic polymer microspheres are widely used in various fields such as chemistry, biomedicine, mechanics, and optoelectronics.
[0004] There have been many literature reports on the synthesis of magnetic polymer microspheres. Currently, there are three main methods for synthesizing magnetic polymer microspheres. The first method is to first synthesize the core of the magnetic particle, and then coat the polymer on the surface of the magnetic particle to form a core-shell structure polymer microsphere; the second method is the opposite structure, first preparing polymer microspheres, then depositing magnetic particles on the outer surface, and then coating the polymer layer to form a sandwich structure; the third method is to first prepare porous microspheres, then deposit magnetic particles in the pores of the microspheres, and coat the outer layer with a polymer layer. The resulting magnetic polymer microspheres have magnetic particles dotted inside the microspheres.
[0005] For the preparation of functional microspheres, the particle size is an important parameter that determines its chemical and physical properties. High uniformity of microsphere size is essential for adjusting particle properties within a narrow range. In specific applications such as drug delivery, pharmaceuticals, and cosmetics, precise control of the size of polymer microspheres and the amount of functional ingredients in the polymer microspheres is required. The term monodisperse particles is used to represent particles with high monodispersity in particle size. A coefficient of variation (CV) of less than 10% is the most commonly used standard for monodispersity, and a better value is less than 5%.
[0006] Patent WO1989004373 describes a method for synthesizing magnetic microspheres with a particle size range of 1-100 μm. In the patent, the first step is to synthesize magnetic particles as the core, the second step is to coat the surface of the magnetic particles with a polymer, and the third step is to coat the outer surface with a layer of polymer with functional groups, and finally obtain magnetic polymer microspheres. The magnetic polymer microspheres can be connected to biological materials such as antigens, antibodies, enzymes, and DNA / RNA hybridization by physical adsorption or covalent bonding. It can be used as a solid phase carrier for different types of immune responses, DNA / RNA hybridization probe detection, affinity purification, and cell sorting. This method belongs to the first method. The magnetic polymer microspheres prepared by this method generally have a wide particle size distribution. At the same time, due to the harsh synthesis conditions of larger magnetic particles, the synthesis of micron-level magnetic spheres is limited, and when the particle size of the magnetic particles increases, it has a negative impact on the performance of the magnetic microspheres, such as superparamagnetism.
[0007] CN1943560A discloses a method for preparing a type of sandwich-structured magnetic composite microspheres with a functionalized shell layer. The magnetic composite microspheres have the following characteristics: a sandwich structure as a whole, a core of polymer microspheres, a middle layer of magnetic nanoparticles, and an outer layer of a functionalized shell layer with a certain thickness. The preparation method belongs to the second method, which generally has high requirements on the preparation equipment, and may have agglomerates or uneven distribution of magnetic particles, resulting in large batch differences in the magnetic polymer microspheres.
[0008] Patent US5976426 introduces a method for preparing magnetic polymer beads, which is to embed magnetic particles on the surface and inside of a hydrophobic polymer matrix to obtain polymer beads. In the patent, a polymer microsphere containing a vinyl functional group is first prepared by a dispersion polymerization method, and then a magnetic fluid is prepared. Then the microspheres and the magnetic fluid are mixed in an organic solvent, and the magnetic fluid penetrates into the shallow layer and surface of the polymer microspheres. After adding an oily initiator, a polymerization monomer and a stabilizer for polymerization reaction, magnetic polymer microspheres are obtained. The preparation method belongs to the third method. This method generally has many steps in the synthesis route, and requires the synthesis of template microspheres, followed by swelling polymerization to prepare porous microspheres, and then adding magnetic particles. The process is relatively complicated.
[0009] The preparation methods of magnetic polymer microspheres in the prior art generally have problems such as harsh synthesis conditions, high requirements for preparation equipment and complex processes. Therefore, it is an issue that cannot be ignored to develop a preparation method for magnetic polymer microspheres with simple process, mild reaction conditions and scalability, and to ensure that the prepared magnetic polymer microspheres have a narrow particle size distribution, tunable magnetic response and good protein adsorption ability. Summary of the invention
[0010] In view of the deficiencies in the prior art, the object of the present invention is to provide a method for preparing magnetic polymer microspheres and applications thereof. The magnetic polymer microspheres are designed with raw materials and process steps so that the obtained magnetic polymer microspheres have narrow particle size distribution, tunable magnetic response and good protein adsorption and coupling capabilities, and can be used for protein separation, purification or coupling.
[0011] To achieve this object, the present invention adopts the following technical solutions:
[0012] In a first aspect, the present invention provides a method for preparing magnetic polymer microspheres, the preparation method comprising the following steps:
[0013] (1) polymerizing the reactive monomer, the first cross-linking agent and the functional monomer to obtain a polymer-based ball;
[0014] (2) reacting the polymer-based spheres obtained in step (1) with a metal salt and an alkaline solution to obtain a mixture, and adding a surfactant to the mixture for a physical reaction to obtain magnetic polymer-based spheres;
[0015] (3) reacting the magnetic polymer-based spheres obtained in step (2) with a monomer and a second cross-linking agent to obtain the magnetic polymer microspheres.
[0016] The invention adopts a three-step method to prepare magnetic polymer microspheres with functional groups on the surface, narrow particle size distribution range (CV<5%), and tunable magnetic response. First, in step (1), the polymer-based ball is a hydrophobic surface polymer-based ball with positive or negative charge on the surface by selecting functional monomers; secondly, in step (2), magnetic particles can be obtained by reacting metal salts and alkaline solutions, and the prepared magnetic particles are hydrophobic magnetic particles with negative or positive charge on the surface by selecting surfactants. Through the two effects of charge attraction and hydrophobic adsorption between the polymer-based ball and the magnetic particles, the magnetic particles are adsorbed on the surface of the polymer-based ball to form magnetic polymer-based balls; finally, in step (3), a polymerization reaction occurs on the outer surface of the magnetic polymer-based ball, so that the polymerization product of the monomer and the cross-linking agent forms a coating on the surface of the magnetic polymer-based ball, that is, a polymer layer is formed on the outer surface of the magnetic polymer-based ball, and different functional groups, such as hydroxyl, amino or carboxyl, can be introduced into the polymer layer according to application requirements. The magnetic particles are wrapped inside by the outer surface polymer layer, which can seal the magnetic particles and prevent the magnetic particles from leaking out, thereby obtaining magnetic polymer microspheres with a sandwich structure. Through the preparation method provided by the present invention, magnetic polymer microspheres of different particle sizes can be synthesized, with narrow particle size distribution, and other properties of the magnetic polymer microspheres can be kept unaffected. At the same time, the synthesis process of the magnetic polymer microspheres is relatively simple, with fewer synthesis steps, mild and controllable reaction conditions, which is conducive to the process of amplification and preparation of magnetic polymer microspheres. By adopting the synergistic effect of the two forces of charge attraction and physical adsorption, the magnetic particles and the polymer-based balls are more firmly combined, the loss of magnetic particles in subsequent steps is reduced, and good magnetic response performance is achieved.
[0017] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.
[0018] As a preferred technical solution, the reactive monomers include a first acrylic ester monomer and / or an aromatic olefin monomer.
[0019] Preferably, the first acrylic ester monomer includes any one of methyl acrylate, methyl methacrylate, butyl acrylate, butyl methacrylate, glycidyl acrylate, glycidyl methacrylate, isooctyl acrylate, isooctyl methacrylate, ethyl acrylate or ethyl methacrylate, or a combination of at least two thereof.
[0020] Preferably, the aromatic olefin monomers include any one of styrene, sodium 4-styrene sulfonate, p-chlorostyrene, p-nitrostyrene, p-methoxystyrene, p-methylstyrene or 2-methylstyrene, or a combination of at least two thereof.
[0021] Preferably, based on the total mass of the reactive monomer, the first cross-linking agent and the functional monomer as 100%, the mass of the reactive monomer is 80%-98.9%, for example, it can be 80%, 81%, 82%, 84%, 86%, 88%, 90%, 92%, 94%, 96%, 98% or 98.9%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0022] Preferably, the first crosslinking agent includes any one or a combination of at least two of ethylene glycol dimethacrylate, ethylene glycol diacrylate, diethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, 1,4-butanediol dimethacrylate, glycerol, 1,3-diisomethacrylate or divinylbenzene.
[0023] Preferably, based on the total mass of the reactive monomer, the first cross-linking agent and the functional monomer as 100%, the mass of the first cross-linking agent is 0.1%-10%, for example, it can be 0.1%, 0.2%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 9.5% or 10%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0024] Preferably, the functional monomer includes any one or a combination of at least two of dimethylaminoethyl acrylate, acrylamide, methylenebisacrylamide, N,N-diethylaminoethyl, dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, 2-(tert-butylamino)ethyl methacrylate, acrylic acid or methacrylic acid.
[0025] Preferably, based on the total mass of the reactive monomer, the first cross-linking agent and the functional monomer as 100%, the mass of the functional monomer is 1%-10%, for example, it can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 9.5% or 10%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0026] As a preferred technical solution, the raw materials for preparing the polymer-based spheres also include a first initiator.
[0027] Preferably, the first initiator includes any one of a first azo initiator, a first peroxide compound initiator or a first persulfate initiator, or a combination of at least two thereof.
[0028] Preferably, the first azo initiator includes any one of azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptanenitrile or dimethyl azobisisobutyrate, or a combination of at least two thereof.
[0029] Preferably, the first peroxide compound initiator comprises benzoyl peroxide.
[0030] Preferably, the first persulfate initiator includes any one of potassium persulfate, sodium persulfate or ammonium persulfate, or a combination of at least two of them.
[0031] Preferably, based on the total mass of the reactive monomer, the first cross-linking agent and the functional monomer as 100%, the mass of the first initiator is 0.1%-10%, for example, it can be 0.1%, 0.2%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 9.5% or 10%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0032] As a preferred technical solution, as a preferred technical solution, the raw materials for preparing the polymer-based balls also include a solvent.
[0033] Preferably, the solvent includes any one of water, anhydrous ethanol, isopropanol, ethyl acetate or n-hexane.
[0034] Preferably, based on the total mass of the reactive monomer, the first cross-linking agent and the functional monomer as 1 part by weight, the mass of the solvent is 5 parts by weight to 100 parts by weight, for example, it can be 5 parts by weight, 10 parts by weight, 20 parts by weight, 30 parts by weight, 40 parts by weight, 50 parts by weight, 60 parts by weight, 70 parts by weight, 80 parts by weight, 90 parts by weight or 100 parts by weight, as well as specific points between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.
[0035] Preferably, the raw materials for preparing the polymer-based spheres further include a stabilizer.
[0036] Preferably, the stabilizer comprises any one of polyvinyl pyrrolidone, polyvinyl alcohol, methyl cellulose, ethyl cellulose, hydroxymethyl cellulose, hydroxymethyl propyl cellulose or hydroxyethyl cellulose, or a combination of at least two thereof.
[0037] Preferably, based on the mass of the solvent as 100%, the mass of the stabilizer is ≤10%, for example, it can be 0%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 9.5% or 10%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0038] Preferably, the raw materials for preparing the polymer-based spheres further include a first emulsifier.
[0039] Preferably, the first emulsifier includes any one of polyoxyethylene sorbitan laurate, polyoxyethylene sorbitan stearate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan monopalmitate, sorbitan laurate, polyoxyethylene octylphenol ether, sodium dodecyl sulfate, sodium dodecyl sulfonate or sodium dodecylbenzene sulfonate, or a combination of at least two thereof.
[0040] Preferably, based on the mass of the solvent as 100%, the mass of the first emulsifier is ≤5%, for example, it can be 0%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0041] Preferably, the polymerization reaction time is 4-36h, for example, it can be 4h, 8h, 12h, 16h, 20h, 24h, 28h, 32h or 36h, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0042] Preferably, the polymerization reaction temperature is 40-90°C, for example, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C or 90°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0043] Preferably, the type of polymerization reaction includes any one of emulsion polymerization, soap-free emulsion polymerization, dispersion polymerization, suspension polymerization or microemulsion polymerization, and one of these methods can be selected to prepare the polymer-based spheres.
[0044] Preferably, the particle size of the polymer-based spheres is 0.1-5 μm, for example, 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0045] As a preferred technical solution, the reaction in step (2) is carried out in the presence of a first solvent.
[0046] Preferably, the first solvent comprises water.
[0047] Preferably, based on the mass of the polymer-based sphere as 1 part by weight, the mass of the first solvent is 5 parts by weight to 100 parts by weight, for example, it can be 5 parts by weight, 10 parts by weight, 20 parts by weight, 30 parts by weight, 40 parts by weight, 50 parts by weight, 60 parts by weight, 70 parts by weight, 80 parts by weight, 90 parts by weight or 100 parts by weight, as well as specific point values between the above-mentioned point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0048] Preferably, the metal salt comprises a combination of a divalent metal salt and a multivalent metal salt, and the multivalent metal salt comprises a trivalent metal salt and / or a hexavalent metal salt.
[0049] Preferably, the divalent metal salt includes any one of a divalent iron salt, a divalent cobalt salt, a divalent nickel salt, a divalent chromium salt or a divalent manganese salt, or a combination of at least two thereof.
[0050] Preferably, the trivalent metal salt includes any one of a trivalent iron salt, a trivalent cobalt salt, a trivalent nickel salt or a trivalent chromium salt, or a combination of at least two thereof.
[0051] Preferably, the hexavalent metal salt comprises potassium manganate.
[0052] Preferably, the divalent metal salt includes any one of ferrous chloride, ferrous sulfate, ferrous ammonium sulfate or manganese sulfate, or a combination of at least two thereof.
[0053] Preferably, the trivalent metal salt includes any one of ferric chloride, ferric sulfate or ammonium ferric sulfate, or a combination of at least two thereof.
[0054] Preferably, the molar ratio of the polyvalent metal salt to the divalent metal salt is 1:(1 / 3-3), for example, it can be 1:1 / 3, 1:2 / 3, 1:1, 1:1.5, 1:2, 1:2.5 or 1:3, as well as specific ratios between the above ratios. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific ratios included in the range.
[0055] Preferably, based on the mass of the polymer-based spheres as 100%, the mass of the metal salt is 10%-80%, for example, it can be 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% or 100%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0056] Preferably, the alkaline solution comprises any one of ammonia water, sodium hydroxide solution, potassium hydroxide solution, sodium carbonate solution, potassium carbonate solution or sodium bicarbonate solution, or a combination of at least two thereof.
[0057] Preferably, the concentration of the alkaline solution is 0.01-17 mol / L, for example, it can be 0.01 mol / L, 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, 3.5 mol / L, 4 mol / L, 4.5 mol / L, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L, 10 mol / L, 11 mol / L, 12 mol / L, 13 mol / L, 14 mol / L, 15 mol / L, 16 mol / L or 17 mol / L, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0058] Preferably, based on the mass of the first solvent as 100%, the mass of the alkaline solution is 5%-50%, for example, it can be 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or 50%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0059] Preferably, the reaction in step (2) is carried out in the presence of a second emulsifier.
[0060] Preferably, the second emulsifier includes any one of polyoxyethylene sorbitan laurate, polyoxyethylene sorbitan stearate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan monopalmitate, sorbitan laurate, polyoxyethylene octylphenol ether, sodium dodecyl sulfate, sodium dodecyl sulfonate or sodium dodecylbenzene sulfonate, or a combination of at least two thereof.
[0061] Preferably, based on the mass of the polymer-based spheres as 100%, the mass of the second emulsifier is 0.01%-20%, for example, it can be 0.01%, 0.1%, 0.5%, 1%, 2%, 3%, 5%, 8%, 11%, 14%, 16%, 18% or 20%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the said range.
[0062] Preferably, the reaction temperature in step (2) is 50-80°C, for example, it can be 50°C, 55°C, 600°C, 65°C, 70°C, 80°C or 85°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0063] Preferably, the reaction time of step (2) is 1-4 h, for example, it can be 1 h, 1.2 h, 1.5 h, 1.8 h, 2 h, 2.2 h, 2.5 h, 2.8 h, 3 h, 3.2 h, 3.5 h, 3.8 h or 4 h, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0064] Preferably, the surfactant comprises any one or a combination of at least two of stearic acid, palmitic acid, lauric acid, oleic acid, 10-undecenoic acid, erucic acid, oleylamine, laurylamine, N,N-dimethyldodecylamine or palmitamine.
[0065] Preferably, based on the mass of the metal salt as 100%, the mass of the surfactant is 5%-50%, for example, it can be 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or 50%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0066] Preferably, the surfactant is used after being diluted with an organic solvent.
[0067] Preferably, the organic solvent includes any one of anhydrous ethanol, methanol, isopropanol or N,N-dimethylformamide, or a combination of at least two thereof.
[0068] Preferably, based on the mass of the surfactant as 1 part by weight, the mass of the organic solvent is 10 parts by weight to 100 parts by weight, for example, it can be 10 parts by weight, 20 parts by weight, 30 parts by weight, 40 parts by weight, 50 parts by weight, 60 parts by weight, 70 parts by weight, 80 parts by weight, 90 parts by weight or 100 parts by weight, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0069] Preferably, the temperature of the physical reaction is 50-80°C, for example, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C, and specific values between the above values. Due to space limitations and for the sake of simplicity, the present invention will no longer exhaustively list the specific values included in the range.
[0070] Preferably, the time of the physical reaction is 1-4h, for example, it can be 1h, 1.2h, 1.5h, 1.8h, 2h, 2.2h, 2.5h, 2.8h, 3h, 3.2h, 3.5h, 3.8h or 4h, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0071] Preferably, the particle size of the magnetic polymer-based spheres is 0.2-6 μm, for example, 0.2 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm or 6 μm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0072] As a preferred technical solution, the monomer in step (3) includes any one of a second acrylic ester monomer, an unsaturated acid monomer or a styrene monomer, or a combination of at least two of them.
[0073] Preferably, the second acrylic ester monomer includes any one of methyl acrylate, methyl methacrylate, butyl acrylate, butyl methacrylate, glycidyl acrylate or glycidyl methacrylate, or a combination of at least two thereof.
[0074] Preferably, the unsaturated acid monomer includes any one of acrylic acid, methacrylic acid or itaconic acid, or a combination of at least two of them.
[0075] Preferably, the styrene monomer includes any one of styrene, α-methylstyrene, 4-methylstyrene or sodium 4-styrene sulfonate, or a combination of at least two thereof.
[0076] Preferably, based on the mass of the magnetic polymer-based ball as 1 part by weight, the mass of the monomer is 0.1 parts by weight to 10 parts by weight, for example, it can be 0.1 parts by weight, 0.5 parts by weight, 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight or 10 parts by weight, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0077] Preferably, the second crosslinking agent includes any one of ethylene glycol dimethacrylate, ethylene glycol diacrylate, diethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, 1,4-butanediol dimethacrylate, polyethylene glycol dimethacrylate or divinylbenzene, or a combination of at least two thereof.
[0078] Preferably, based on the mass of the monomer as 100%, the mass of the second cross-linking agent is 0.1%-10%, for example, it can be 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0079] Preferably, the raw materials for preparing the magnetic polymer microspheres further include a second initiator.
[0080] Preferably, the second initiator includes any one of a second azo initiator, a second peroxide compound initiator or a second persulfate initiator, or a combination of at least two thereof.
[0081] Preferably, the second azo initiator includes any one of azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate or azobisisobutyramidine hydrochloride, or a combination of at least two thereof.
[0082] Preferably, the second peroxide compound initiator comprises benzoyl peroxide.
[0083] Preferably, the second persulfate initiator includes any one of potassium persulfate, sodium persulfate or ammonium persulfate, or a combination of at least two of them.
[0084] Preferably, based on the mass of the monomer in step (3) as 100%, the mass of the second initiator is 0.5%-5%, for example, it can be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the said range.
[0085] Preferably, the raw materials for preparing the magnetic polymer microspheres further include an emulsifier solution.
[0086] Preferably, the solute in the emulsifier solution includes any one or a combination of at least two of polyoxyethylene sorbitan laurate, polyoxyethylene sorbitan stearate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan monopalmitate, sorbitan laurate, polyoxyethylene octylphenol ether, sodium dodecyl sulfate, sodium dodecyl sulfonate or sodium dodecylbenzene sulfonate.
[0087] Preferably, the solvent in the emulsifier solution includes any one of water, ethanol, methanol or isopropanol.
[0088] Preferably, the solute mass fraction of the emulsifier solution is 0.01%-5%, for example, it can be 0.01%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0089] Preferably, based on the mass of the monomer in step (3) being 1 part by weight, the mass of the emulsifier solution is 5 parts by weight to 20 parts by weight, for example, it can be 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, 10 parts by weight, 11 parts by weight, 12 parts by weight, 13 parts by weight, 14 parts by weight, 15 parts by weight, 16 parts by weight, 17 parts by weight, 18 parts by weight, 19 parts by weight or 20 parts by weight, as well as specific points between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.
[0090] Preferably, the reaction in step (3) is carried out in the presence of a second solvent.
[0091] Preferably, the second solvent comprises water.
[0092] Preferably, based on the mass of the magnetic polymer-based ball as 1 part by weight, the mass of the second solvent is 5 parts by weight to 100 parts by weight, for example, it can be 5 parts by weight, 10 parts by weight, 20 parts by weight, 30 parts by weight, 40 parts by weight, 50 parts by weight, 60 parts by weight, 70 parts by weight, 80 parts by weight, 90 parts by weight or 100 parts by weight, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0093] Preferably, the reaction temperature in step (3) is 50-85°C, for example, it can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C or 85°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0094] Preferably, the reaction time of step (3) is 4-24 h, for example, it can be 4 h, 6 h, 8 h, 10 h, 12 h, 14 h, 16 h, 18 h, 20 h, 22 h or 24 h, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0095] As a preferred technical solution, the preparation method specifically comprises the following steps:
[0096] (1) A reaction monomer, a first cross-linking agent, a functional monomer, a solvent, a first initiator, a stabilizer and a first emulsifier are mixed and then subjected to a polymerization reaction to obtain a polymer-based ball.
[0097] Taking the total mass of the reactive monomer, the first crosslinking agent and the functional monomer as 100%, the mass of the reactive monomer is 80%-98.9%, the mass of the first crosslinking agent is 0.1%-10%, the mass of the functional monomer is 1%-10%, and the mass of the first initiator is 0.1%-10%.
[0098] Based on 1 part by weight of the total weight of the reactive monomer, the first cross-linking agent and the functional monomer, the weight of the solvent is 5 parts by weight to 100 parts by weight.
[0099] Based on the mass of the solvent being 100%, the mass of the stabilizer is ≤10%, and the mass of the first emulsifier is ≤5%.
[0100] The polymerization reaction time is 4-36h.
[0101] The polymerization temperature is 40-90°C.
[0102] The particle size of the polymer-based spheres is 0.1-5 μm.
[0103] After the polymerization reaction is completed, the step of washing the polymer-based balls by centrifugation, filtration or dialysis is also included.
[0104] (2) The polymer-based spheres obtained in step (1) are mixed with a first solvent, a metal salt, an alkaline solution and a second emulsifier, and the mixture is reacted to obtain a mixture, and a surfactant and an organic solvent are added to the mixture to carry out a physical reaction to obtain magnetic polymer-based spheres.
[0105] Based on 1 part by weight of the polymer-based spheres, the mass of the first solvent is 5 parts by weight to 100 parts by weight.
[0106] The metal salt includes a combination of a divalent metal salt and a multivalent metal salt, and the multivalent metal salt includes a trivalent metal salt and / or a hexavalent metal salt.
[0107] The molar ratio of the multivalent metal salt to the divalent metal salt is 1:(1 / 3-3).
[0108] Based on 100% of the mass of the polymer-based ball, the mass of the metal salt is 10%-80%, and the mass of the second emulsifier is 0.01%-20%.
[0109] Taking the mass of the first solvent as 100%, the mass of the alkaline solution is 5%-50%.
[0110] The concentration of the alkaline solution is 0.01-17 mol / L.
[0111] Based on the mass of the metal salt being 100%, the mass of the surfactant is 5%-50%.
[0112] Based on 1 part by weight of the surfactant, the amount of the organic solvent is 10 parts by weight to 100 parts by weight.
[0113] The reaction temperature is 50-80°C.
[0114] The reaction time is 1-4h.
[0115] The temperature of the physical reaction is 50-80°C.
[0116] The physical reaction time is 1-4h.
[0117] The particle size of the magnetic polymer-based sphere is 0.2-6 μm.
[0118] The alkaline solution is mixed with the polymer-based balls, the first solvent, the metal salt and the second emulsifier in a dropwise manner to react, and the dropwise addition time is 0.5-3 hours.
[0119] The surfactant and the organic solvent are mixed and then added dropwise to the mixture to undergo a physical reaction. The time for the addition of the surfactant and the organic solvent is 0.5-2 hours.
[0120] After the physical reaction is completed, the magnetic polymer-based balls and the reaction solution are separated by centrifugation at room temperature, and the magnetic polymer-based balls are washed with a cleaning solvent, wherein the cleaning solvent includes any one of deionized water, anhydrous ethanol, methanol or isopropanol, or a combination of at least two of them.
[0121] (3) The magnetic polymer-based spheres obtained in step (2) are mixed with monomers, a second cross-linking agent, a second initiator, an emulsifier solution and a second solvent, and then reacted to obtain the magnetic polymer microspheres.
[0122] Based on 1 part by weight of the magnetic polymer-based sphere, the mass of the monomer is 0.1 parts by weight to 10 parts by weight, and the mass of the second solvent is 5 parts by weight to 100 parts by weight.
[0123] Based on 100% of the mass of the monomer, the mass of the second cross-linking agent is 0.1%-10%, and the mass of the second initiator is 0.5%-5%.
[0124] Based on 1 part by weight of the monomer, the mass of the emulsifier solution is 5 parts by weight to 20 parts by weight.
[0125] The solute mass fraction of the emulsifier solution is 0.01%-5%.
[0126] The reaction temperature is 50-85°C.
[0127] The reaction time is 4-24h.
[0128] In order to reduce the reaction rate and prevent the agglomeration of the magnetic polymer microspheres, the monomer, the second crosslinking agent, the second initiator, the emulsifier solution and the second solvent are first mixed and then mixed with the magnetic polymer-based spheres in a dropwise manner, and the dropping time is 0.5-3h.
[0129] After the reaction in step (3) is completed, the method further comprises separating the magnetic polymer microspheres from the reaction solution, washing the magnetic polymer microspheres 3-6 times with a solvent, and then adding deionized water to disperse the microspheres and storing them at 2-8°C.
[0130] In a second aspect, the present invention provides a magnetic polymer microsphere, wherein the magnetic polymer microsphere is prepared by the preparation method described in the first aspect.
[0131] Preferably, the particle size of the magnetic polymer microspheres is 0.3-8 μm, for example, 0.3 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm or 8 μm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0132] Preferably, the particle size of the magnetic polymer microspheres is 1.4-5.5 μm, for example, it can be 1.4 μm, 2.2 μm, 2.6 μm, 2.9 μm, 3.3 μm, 3.6 μm, 3.9 μm, 4.2 μm, 4.6 μm, 4.9 μm, 5.2 μm or 5.5 μm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0133] Preferably, the coefficient of variation of the magnetic polymer microspheres is 3-5%.
[0134] In a third aspect, the present invention provides a use of the magnetic polymer microspheres as described in the second aspect in the separation, purification or coupling of proteins.
[0135] Compared with the prior art, the present invention has the following beneficial effects:
[0136] The preparation method of the magnetic polymer microspheres provided by the invention is relatively simple, has fewer synthesis steps, and has mild and controllable reaction conditions, which is conducive to the process-scaled preparation of the magnetic polymer microspheres. The magnetic polymer microspheres with different particle sizes can be synthesized, and the particle size distribution is narrow, with a CV of 3-5%, and other properties of the magnetic polymer microspheres can be kept unaffected. The combination between the magnetic particles and the polymer-based balls is more firm, which can reduce the loss of the magnetic particles in the subsequent steps and has good magnetic response performance. The prepared magnetic polymer microspheres are nearly spherical, have good uniformity, and have high protein adsorption capacity. When the concentration of streptavidin reaches 60 μg / mg, the adsorption efficiency can still reach 72-76%. In addition, the magnetic polymer microspheres provided by the invention also have good protein coupling efficiency, with a coupling efficiency of 96.11-98.17%, and can be applied to the separation, purification or coupling of proteins. BRIEF DESCRIPTION OF THE DRAWINGS
[0137] Figure 1 is a scanning electron microscope image of the magnetic polymer microspheres provided in Example 2;
[0138] Figure 2 This is a scanning electron microscope image of the magnetic polymer microspheres provided in Example 5. DETAILED DESCRIPTION
[0139] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0140] The sources of some components in the following examples and comparative examples are as follows:
[0141] (1) Polyvinylpyrrolidone: Aladdin, CAS 9003-39-8, weight average molecular weight 58000;
[0142] (2) Polyoxyethylene sorbitan stearate: Aladdin, CAS 9005-67-8, molecular weight 1311.68;
[0143] (3) Polyoxyethylene sorbitan laurate: Aladdin, CAS 9005-64-5, molecular weight 346.46;
[0144] (4) PBS: Adamas life, concentration 1×, pH 7.2-7.4;
[0145] (5) SA: Solarbio, CAS 9013-20-1, molecular weight 55 kDa;
[0146] (6) 2-Morpholineethanesulfonic acid (MES): Bioss, 0.1 mol / L;
[0147] (7) 1-Ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride: Aladdin, CAS
[0148] 25925-53-8, molecular weight is 191.7.
[0149] Example 1
[0150] A method for preparing magnetic polymer microspheres, the preparation method comprising the following steps:
[0151] (1) 10 g of methyl methacrylate, 0.1 g of diethylene glycol dimethacrylate, 0.5 g of dimethylaminoethyl methacrylate, 0.02 g of azobisisobutyronitrile and 100 g of anhydrous ethanol were added to a flask, and mechanical stirring was started to mix well. The stirring speed was set to 300 rpm, and then 1 g of polyvinyl pyrrolidone was added. After nitrogen was introduced for 30 minutes, the introduction of nitrogen was stopped. The reaction temperature was 70°C and the reaction was carried out for 18 hours. After the reaction was completed, the temperature was lowered to room temperature, and the reaction solution was centrifuged to obtain polymer-based balls. After 100 g of anhydrous ethanol was used, the ball was dispersed on a roller oscillator for 30 minutes, and then centrifuged again. After washing three times, 200 g of deionized water was used to wash three times in the same way, and finally an appropriate amount of deionized water was added to preserve the obtained polymer-based balls.
[0152] (2) 8 g of the polymer-based ball obtained in step (1) was dispersed by adding 80 g of deionized water, and then transferred to a reaction flask, 0.5 g of polyoxyethylene sorbitan stearate was added, mechanically stirred and dispersed, and nitrogen was introduced. 1.5 g of ferric chloride and 1.5 g of ferrous chloride were weighed, and each was dissolved in 10 g of deionized water and added to the flask. 20 g of 1 mol / L sodium hydroxide solution was added to a constant pressure dropping funnel and sealed. When the temperature of the reaction solution reached 70°C, the sodium hydroxide solution was added dropwise, and the addition was completed in 1 hour, and the reaction was continued for 3 hours. 0.3 g of oleic acid was weighed, diluted with 30 g of anhydrous ethanol, and added to a constant pressure dropping funnel. The addition was completed in 30 minutes, and the reaction was stopped after the reaction was continued for 1 hour. After the reaction solution cooled to room temperature, the magnetic polymer-based ball was obtained by centrifugation, washed 3 times with 100 g of anhydrous ethanol, and then washed 3 times with 100 g of deionized water, and an appropriate amount of water was added for dispersion.
[0153] (3) 8 g of the magnetic polymer-based ball obtained in step (2) was added to 150 g of deionized water for dispersion and then transferred to a reaction flask. 5 g of styrene, 0.5 g of divinylbenzene, 0.1 g of azobisisoheptanenitrile and 30 g of a sodium dodecylbenzene sulfonate solution with a solute mass fraction of 1% were added to a beaker, dispersed for 30 minutes using a high-speed stirrer, and then added to a constant pressure dropping funnel. When the temperature of the solution in the reaction flask reached 65° C., the addition was started, and the addition was stopped after 50 minutes. The reaction was stopped after another 6 hours of reaction. The reaction solution was centrifuged to obtain magnetic polymer microspheres, which were washed 3 times with anhydrous ethanol and deionized water, 200 g each time, respectively. After removing the supernatant, deionized water was added for dispersion and storage. The particle size of the magnetic polymer microspheres was 5 μm and the CV was 3.23%.
[0154] Example 2
[0155] A method for preparing magnetic polymer microspheres, the preparation method comprising the following steps:
[0156] (1) Add 20 g of styrene, 0.1 g of divinylbenzene, 1 g of acrylic acid, 0.05 g of azobisisobutyronitrile and 150 g of isopropanol into a flask, start mechanical stirring to mix, and set the stirring speed to 350 rpm. Then add 3 g of polyvinyl pyrrolidone, and stop passing nitrogen after 60 minutes. The reaction temperature is 65°C and the reaction is carried out for 16 hours. After the reaction is completed, the temperature is lowered to room temperature, and the reaction solution is centrifuged to obtain polymer-based balls. Use 200 g of isopropanol and disperse on a roller oscillator for 30 minutes, then centrifuge again. After washing three times, use 200 g of deionized water and wash three times in the same way. Finally, add an appropriate amount of deionized water to preserve the obtained polymer-based balls.
[0157] (2) Take 18g of the polymer-based ball obtained in step (1), add 100g of deionized water to disperse and transfer to a round-bottom flask, add 0.5g of polyoxyethylene sorbitan laurate, mechanically stir and disperse, and start to introduce argon. Weigh 2g of ferric chloride and 4g of ferrous sulfate, respectively, and dissolve them in 50g of deionized water and add them to the flask. Take 50g of 14.7mol / L ammonia water and add it to a constant pressure dropping funnel and seal it. When the temperature of the reaction solution reaches 70°C, start to add ammonia water, add it dropwise for 1h, continue to react for 30min and then stop the reaction. Weigh 0.3g of palmitamine, dilute it with 30g of isopropanol, add it to the constant pressure dropping funnel, add it dropwise for 50min, and stop the reaction after 0.5h of reaction. After the reaction solution cools to room temperature, centrifuge to obtain the magnetic polymer-based ball, wash it 3 times with 150g of isopropanol, then wash it 3 times with 150g of deionized water, add appropriate amount of water and disperse it for use.
[0158] (3) Take 18g of the magnetic polymer-based ball obtained in step (2), add 200g of deionized water to disperse, and then transfer to a reaction flask, add 2.5g of glycidyl methacrylate, 0.5g of methacrylic acid, 0.2g of 1,4-butanediol dimethacrylate, 0.1g of azobisisovaleronitrile and 50g of sodium dodecylbenzene sulfonate solution with a solute mass fraction of 1% to a beaker, disperse with a high-speed stirrer for 15 minutes, and then add to a constant pressure dropping funnel. When the temperature of the solution in the flask reaches 55°C, start dropping, and stop dropping after 50 minutes. After reacting for another 4 hours, stop the reaction. The reaction solution is centrifuged to obtain magnetic polymer microspheres, which are washed 3 times with isopropanol and deionized water, 200g each time, and after removing the supernatant, add deionized water to disperse and store. The particle size of the magnetic polymer microspheres is 5.2μm and the CV is 3.17%.
[0159] Example 3
[0160] A method for preparing magnetic polymer microspheres, the preparation method comprising the following steps:
[0161] (1) Add 30 g of methyl methacrylate, 1 g of tetraethylene glycol dimethacrylate, 2 g of diethylaminoethyl methacrylate, 0.5 g of potassium persulfate and 300 g of water into a flask, start mechanical stirring to mix, and set the stirring speed to 200 rpm. Then add 0.1 g of sodium dodecyl sulfate, and stop passing nitrogen after passing nitrogen for 60 minutes. The reaction temperature is 70°C and the reaction is carried out for 20 hours. After the reaction is completed, the temperature is lowered to room temperature, and the reaction solution is centrifuged to obtain polymer-based balls. Use 500 g of ethanol, and disperse on a roller oscillator for 30 minutes, and then centrifuge again. After washing three times, use 500 g of deionized water and wash three times in the same way. Finally, add an appropriate amount of deionized water to preserve the obtained polymer-based balls.
[0162] (2) Take 15g of the polymer-based balls obtained in step (1), add 200g of deionized water to disperse and transfer to a round-bottom flask, add 1g of sorbitan laurate, stir mechanically to disperse, and start to introduce argon. Weigh 2g of manganese sulfate and 3.2g of ferric chloride respectively, dissolve them in 20g of deionized water and add them to the flask. Transfer 40g of 1mol / L sodium hydroxide solution to a constant pressure dropping funnel and seal it. When the temperature of the reaction solution reaches 70°C, start dropping and complete the addition in 1h. Continue the reaction for 1h and then stop the reaction. Weigh 1g of oleic acid, dilute it with 50g of ethanol, add it to the constant pressure dropping funnel, add it dropwise for 0.5h, and stop the reaction after 0.5h. After the reaction solution cools to room temperature, centrifuge to obtain magnetic polymer-based balls, wash them 3 times with 200g of ethanol, and then wash them 3 times with 200g of deionized water, add appropriate amount of water to disperse for use.
[0163] (3) Take 15g of the magnetic polymer-based ball obtained in step (2), centrifuge to remove the dispersion liquid, disperse it in 200g of deionized water and transfer it to a reaction flask, add 5g of butyl methacrylate, 1g of acrylic acid, 0.2g of ethylene glycol dimethacrylate, 0.1g of azobisisobutyronitrile and 30g of sodium dodecylsulfonate solution with a solute mass fraction of 5% into a beaker, disperse it with a high-speed stirrer for 30 minutes, and then add it to a constant pressure dropping funnel. When the temperature of the solution in the flask reaches 65°C, start dropping, and stop dropping after 2h. After reacting for another 12h, stop the reaction. Centrifuge the reaction solution to obtain magnetic polymer microspheres, wash them with methanol and water three times, 200g each time, remove the supernatant, add deionized water to disperse and store, the particle size of the magnetic polymer microspheres is 4.9μm, and the CV is 4.01%.
[0164] Example 4
[0165] (1) 16 g of methyl acrylate, 2 g of ethylene glycol diacrylate, 2 g of acrylamide, 0.3 g of sodium persulfate and 200 g of water were added to a flask, and the mechanical stirring was turned on to mix well. The stirring speed was set to 200 rpm. Then 0.5 g of sodium dodecylbenzene sulfonate was added and nitrogen was introduced for 45 minutes. The reaction temperature was set to 75 ° C and the reaction was carried out for 24 hours. After the reaction was completed, the temperature was lowered to room temperature, and the reaction solution was centrifuged to obtain polymer-based balls. After 200 g of ethanol was used, the ball was dispersed on a roller oscillator for 30 minutes, and then centrifuged again. After washing three times, it was washed three times with 200 g of deionized water in the same way. Finally, an appropriate amount of deionized water was added to preserve the obtained polymer-based balls.
[0166] (2) Take 10g of the polymer-based ball obtained in step (1), add 150g of deionized water to disperse and transfer to a round-bottom flask, add 2g of polyoxyethylene sorbitan monopalmitate, stir mechanically to disperse, and start to introduce nitrogen. Weigh 1.5g of ferrous chloride and 1.5g of ferric chloride respectively, dissolve them in 25g of deionized water and add them to the flask respectively. Transfer 60g of 0.5mol / L potassium hydroxide solution to a constant pressure dropping funnel and seal it. When the temperature of the reaction solution reaches 60°C, start to drop potassium hydroxide solution, add it dropwise for 1.5h, continue to react for 1.5h and stop the reaction. Weigh 1.5g of palmitic acid, dilute it with 50g of methanol, add it to the constant pressure dropping funnel, add it dropwise for 0.5h, and stop the reaction after 0.5h. After the reaction solution cools to room temperature, centrifuge to obtain magnetic polymer-based balls, wash them with 200g of ethanol 3 times, and then wash them with 200g of deionized water 3 times, add appropriate amount of water to disperse them for use.
[0167] (3) Take 10g of the magnetic polymer-based ball obtained in step (2), centrifuge to remove the dispersion liquid, disperse it with 200g of deionized water and transfer it to a reaction flask, add 8g of sodium 4-styrenesulfonate, 2g of itaconic acid, 1g of polyethylene glycol dimethacrylate, 0.5g of azobisisobutyronitrile and 60g of sodium dodecylbenzenesulfonate solution with a solute mass fraction of 2% into a beaker, disperse it with a high-speed stirrer for 30 minutes, and then add it to a constant pressure dropping funnel. When the temperature of the solution in the flask reaches 72°C, start dropping, and stop dropping after 1.5h. After reacting for 16h, stop the reaction. Centrifuge the reaction solution to obtain magnetic polymer microspheres, wash them with ethanol and water for 3 times, 200g each time, remove the supernatant, add deionized water to disperse and store, the particle size of the magnetic polymer microspheres is 5.5μm, and the CV is 3.89%.
[0168] Example 5
[0169] (1) 18 g of glycidyl methacrylate, 2 g of divinylbenzene, 2 g of methacrylic acid, 0.3 g of potassium persulfate and 200 g of water were added to a flask, and mechanical stirring was started to mix well. The stirring speed was set to 200 rpm. 0.5 g of sodium dodecylbenzene sulfonate was then added, and nitrogen was introduced for 60 minutes and then stopped. The reaction temperature was 70°C and the reaction was continued for 18 hours. After the reaction was completed, the temperature was lowered to room temperature, and the reaction solution was centrifuged to obtain polymer-based balls. The polymer-based balls were dispersed on a roller oscillator with 200 g of isopropanol for 30 minutes and then centrifuged again. After washing three times, the polymer-based balls were washed three times with 200 g of deionized water in the same way. Finally, an appropriate amount of deionized water was added to preserve the polymer-based balls.
[0170] (2) 10 g of the polymer-based balls obtained in step (1) were added to 150 g of deionized water and dispersed into a reaction flask, 2 g of polyoxyethylene sorbitan laurate was added, mechanically stirred and dispersed, and nitrogen was introduced. 1.5 g of ferrous sulfate and 1.5 g of ferrous sulfate were weighed, and they were dissolved in 25 g of deionized water and added to the flask. 60 g of 0.5 mol / L sodium hydroxide solution was transferred to a constant pressure dropping funnel and sealed. When the temperature of the reaction solution reached 60 ° C, sodium hydroxide solution was added dropwise, and the addition was completed after 1 h. The reaction was continued for 1 h and then stopped. 1.5 g of oleic acid was weighed, diluted with 50 g of methanol, and added to a constant pressure dropping funnel. The addition was completed after 0.5 h, and the reaction was stopped after 0.5 h. After the reaction solution was cooled to room temperature, the magnetic polymer-based balls were centrifuged to obtain the magnetic polymer-based balls, washed 3 times with 200 g of anhydrous ethanol, and then washed 3 times with 200 g of deionized water, and an appropriate amount of water was added to disperse for use.
[0171] (3) Take 10g of the magnetic polymer-based ball obtained in step (2), centrifuge to remove the dispersion liquid, disperse it with 200g of deionized water and transfer it to a reaction flask, add 8g of glycidyl methacrylate, 2g of acrylic acid, 1g of ethylene glycol dimethacrylate, 0.5g of azobisisovaleronitrile and 60g of sodium dodecylbenzene sulfonate solution with a solute mass fraction of 2% into a beaker, disperse it with a high-speed stirrer for 30 minutes, and then add it to a constant pressure dropping funnel. When the temperature of the solution in the flask reaches 52°C, start dropping, and stop dropping after 1.5h. After reacting for 16h, stop the reaction. Centrifuge the reaction solution to obtain magnetic polymer microspheres, wash them with ethanol and water for 3 times, 200g each time, remove the supernatant, add deionized water to disperse and store, the particle size of the magnetic polymer microspheres is 1.4μm, and the CV is 3.05%.
[0172] Comparative Example 1
[0173] (1) 16 g of methyl acrylate, 2 g of ethylene glycol diacrylate, 2 g of acrylamide, 0.3 g of sodium persulfate and 200 g of water were added to a flask, and mechanical stirring was started to mix well. The stirring speed was set to 200 rpm. Then 0.5 g of sodium dodecylbenzene sulfonate was added and nitrogen was introduced for 45 minutes. The reaction temperature was set to 75 ° C and the reaction was allowed to proceed for 24 hours. After the reaction was completed, the temperature was lowered to room temperature, and the reaction solution was centrifuged to obtain polymer-based balls. The polymer-based balls were dispersed on a roller oscillator with 200 g of ethanol for 30 minutes and then centrifuged again. After washing three times, the polymer-based balls were washed three times with 200 g of deionized water in the same way. Finally, an appropriate amount of deionized water was added to preserve the obtained polymer-based balls.
[0174] (2) Weigh 1.5 g of ferrous chloride and 1.5 g of ferric chloride respectively, dissolve them in 100 g of deionized water and add them to a flask. Pipette 60 g of 0.5 mol / L potassium hydroxide solution into a constant pressure dropping funnel and seal it. When the temperature of the reaction solution reaches 60°C, start adding potassium hydroxide solution dropwise. The addition is completed after 1.5 hours. Continue the reaction for 1 hour and then stop the reaction to obtain a magnetic particle dispersion.
[0175] (3) Take 10 g of the polymer-based balls obtained in step (1), centrifuge to remove deionized water, and then disperse the polymer-based balls with the magnetic particle dispersion in step (2), and then transfer them into a reaction flask, and set the temperature to 60° C. Weigh 1.5 g of palmitic acid, dilute it with 50 g of methanol, add it to a constant pressure dropping funnel, add it dropwise for 0.5 h, stop the reaction after 0.5 h, centrifuge the reaction solution, wash it three times with 200 g of ethanol and 200 g of water respectively, and finally add an appropriate amount of water to disperse it for use.
[0176] (4) Take 10g of the magnetic polymer-based ball obtained in step (3), centrifuge to remove the dispersion liquid, disperse it with 200g of deionized water and transfer it to a reaction flask, add 8g of sodium 4-styrenesulfonate, 2g of itaconic acid, 1g of polyethylene glycol dimethacrylate, 0.5g of azobisisobutyronitrile and 60g of a sodium dodecylbenzenesulfonate solution with a solute mass fraction of 2% into a beaker, disperse it with a high-speed stirrer for 30 minutes, and then add it to a constant pressure dropping funnel. When the temperature of the solution in the flask reaches 72°C, start dropping, and stop dropping after 1.5h. After reacting for 16h, stop the reaction. Centrifuge the reaction solution to obtain magnetic polymer microspheres, wash them with ethanol and water for 3 times, 200g each time, remove the supernatant, add deionized water to disperse and store, the particle size of the magnetic polymer microspheres is 5.4μm, and the CV is 3.55%.
[0177] Performance Test:
[0178] (1) Scanning electron microscope (Regulus8100, Hitachi) was used to scan the magnetic polymer microspheres to be tested;
[0179] (2) Particle size distribution test: The CV value was obtained by using a laser diffraction particle size analyzer (Beckman Coulter, LS13320XR);
[0180] (3) Streptavidin (SA) adsorption rate test:
[0181] First, PBS (1×) solution was used to prepare streptavidin solutions of different concentrations of 10 μg / mL, 20 μg / mL, 30 μg / mL, 40 μg / mL, 50 μg / mL, and 60 μg / ml, and the concentration of streptavidin was determined using an ultra-micro UV-visible analyzer (UV5Nano Mettler Toledo). Weigh 100 mg of the magnetic polymer microspheres provided in Example 1 into 6 1.5 mL centrifuge tubes as a group, repeat this operation, and weigh 100 mg of the magnetic polymer microspheres provided in Example 2, Example 3, Example 4, and Comparative Example 1 into 6 1.5 mL centrifuge tubes, for a total of five groups. Taking one group as an example, the supernatant solution was removed after magnetic absorption, and after washing three times with 1 mL of PBS (1×) solution, the supernatant was removed by magnetic absorption separation of a magnetic stand, and then 1 mL of the streptavidin solution of different concentrations prepared above was added in turn, vortexed and dispersed, and then placed in a 30°C chromatography cabinet for incubation for 1 hour. After magnetic separation, the supernatant was removed and transferred into a 1.5 mL centrifuge tube for storage. Finally, the concentration of streptavidin in the supernatant solution was determined using an ultra-micro UV-visible analyzer. The adsorption rate was calculated according to the formula A(%) = [C1–C2] / C1×100%, where C1 is the concentration of streptavidin and C2 is the concentration of streptavidin in the supernatant solution, and the percentage of streptavidin bound to the surface of magnetic polymer microspheres in the total streptavidin was obtained. The results are shown in Table 1:
[0182] Table 1
[0183] SA concentration (ug / mL) 10 20 30 40 50 60 Example 1 100% 100% 100% 92% 85% 72% Example 2 100% 100% 100% 90% 83% 76% Example 3 100% 100% 100% 92% 86% 75% Example 4 100% 100% 100% 93% 87% 72% Comparative Example 1 82% 70% 50% 42% 31% 25%
[0184] It can be seen from Table 1 that when the concentration of streptavidin is 40 μg / mL, the adsorption efficiency of Examples 1-4 reaches more than 90%. Compared with Example 4, Comparative Example 1 has a lower adsorption efficiency due to the less and uneven distribution of magnetic particles on the microspheres. When the concentration of streptavidin is 40 μg / mL, the adsorption efficiency is only 42%, indicating that the magnetic polymer microspheres provided by the present invention have good protein adsorption efficiency and are suitable for applications such as protein separation and purification.
[0185] (4) Protein coupling efficiency test:
[0186] The magnetic polymer microspheres provided in Examples 1-4 and Comparative Example 1 are marked as five groups, A, B, C, D, and E, respectively. Under the same experimental conditions, a one-step method was used to couple streptavidin, and the streptavidin coupling efficiency was determined. The experimental method is as follows: (1) Pipette dispersions A to E containing 100 mg of magnetic polymer microspheres in turn, put them into 5 10 mL sample bottles, remove the supernatant dispersion by magnetic suction, and vortex wash three times with 0.1 mol / L MES solution with a pH of 5 (marked as solution a). After magnetic separation of the magnetic spheres, remove the supernatant, add 2 mL of solution a, and set aside; (2) Take 20 mL of solution a into a 50 mL sample bottle, put it in an ice water bath and cool for 20 minutes, then weigh 1-ethyl-(3-dimethylaminopropyl)propane 0.1 g of 1,2-diaminobenzyl carbodiimide hydrochloride was quickly added to a 50 mL sample bottle to obtain solution b. After vortexing for 10 seconds, 2 mL of solution b was pipetted and added to the sample bottle in step (1). After vortexing, the solution was placed in a chromatography cabinet at 25° C. for reaction for 30 minutes. (3) Preparation of streptavidin solution: 60 mg of streptavidin solid was weighed, 6 mL of solution a was added, and the solution was mixed by roller for 30 minutes. The concentration of streptavidin was determined by ultra-micro UV-visible analyzer (UV5Nano Mettler Toledo). 总 , set aside; (4) After the reaction of step (2) is completed, remove the reaction solution by magnetic suction and wash with solution a 3 times, 4 mL each time. After removing the supernatant, add 3 mL of solution a and vortex to disperse, then add 1 mL of SA solution from step (3), put it in a chromatography cabinet and react at 25°C for 30 minutes. After completion, separate the polymer microspheres and the reaction solution by magnetic suction, take the supernatant, and use an ultra-micro UV-visible analyzer to determine the concentration of streptavidin C 上 The coupling efficiency was calculated according to the formula: D (%) = [C 总 – 4×C 上 ] / C 总 ×100%, the test and calculation results are shown in Table 2:
[0187] Table 2
[0188] sample Example 1 Example 2 Example 3 Example 4 Comparative Example 1 <![CDATA[C 总 ]]> 9.860 9.860 9.860 9.860 9.860 <![CDATA[C 上 ]]> 0.045 0.086 0.079 0.096 0.451 Coupling efficiency D 98.17% 96.51% 96.80% 96.11% 81.7%
[0189] As shown in Table 2, the coupling efficiency of Examples 1-4 is above 95%, while that of Comparative Example 1 is only 81.7%, which is significantly lower than that of the Examples. This indicates that the magnetic polymer microspheres prepared by the present invention have good protein coupling efficiency and are suitable for subsequent applications such as immunization.
[0190] Figure 1 and Figure 2 They are scanning electron microscope images of the magnetic polymer microspheres provided in Example 2 and Example 5, respectively. It can be seen from the images that the magnetic polymer microspheres are nearly spherical, with a rough surface, small protrusions, and good uniformity.
[0191] The applicant declares that the present invention illustrates the detailed process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing magnetic polymer microspheres, characterized in that: The preparation method comprises the following steps: (1) polymerizing the reactive monomer, the first cross-linking agent and the functional monomer to obtain a polymer-based ball; (2) reacting the polymer-based spheres obtained in step (1) with a metal salt and an alkaline solution to obtain a mixture, and adding a surfactant to the mixture for a physical reaction to obtain magnetic polymer-based spheres; (3) reacting the magnetic polymer-based spheres obtained in step (2) with a monomer and a second cross-linking agent to obtain the magnetic polymer microspheres.
2. The preparation method according to claim 1, characterized in that: The reactive monomers include a first acrylic ester monomer and / or an aromatic olefin monomer; Preferably, the first acrylic acid ester monomer includes any one of methyl acrylate, methyl methacrylate, butyl acrylate, butyl methacrylate, glycidyl acrylate, glycidyl methacrylate, isooctyl acrylate, isooctyl methacrylate, ethyl acrylate or ethyl methacrylate, or a combination of at least two thereof; Preferably, the aromatic olefin monomers include any one or a combination of at least two of styrene, sodium 4-styrene sulfonate, p-chlorostyrene, p-nitrostyrene, p-methoxystyrene, p-methylstyrene or 2-methylstyrene; Preferably, based on the total mass of the reactive monomer, the first cross-linking agent and the functional monomer being 100%, the mass of the reactive monomer is 80%-98.9%; Preferably, the first cross-linking agent comprises any one or a combination of at least two of ethylene glycol dimethacrylate, ethylene glycol diacrylate, diethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, 1,4-butanediol dimethacrylate, glycerol, 1,3-diisomethacrylate or divinylbenzene; Preferably, based on the total mass of the reactive monomer, the first cross-linking agent and the functional monomer being 100%, the mass of the first cross-linking agent is 0.1%-10%; Preferably, the functional monomer includes any one or a combination of at least two of dimethylaminoethyl acrylate, acrylamide, methylenebisacrylamide, N,N-diethylaminoethyl, dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, 2-(tert-butylamino)ethyl methacrylate, acrylic acid or methacrylic acid; Preferably, based on the total mass of the reactive monomer, the first cross-linking agent and the functional monomer being 100%, the mass of the functional monomer is 1%-10%.
3. The preparation method according to claim 1 or 2, characterized in that: The raw materials for preparing the polymer-based ball also include a first initiator; Preferably, the first initiator comprises any one of a first azo initiator, a first peroxide compound initiator or a first persulfate initiator, or a combination of at least two thereof; Preferably, the first azo initiator includes any one of azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptanenitrile or dimethyl azobisisobutyrate, or a combination of at least two thereof; Preferably, the first peroxide compound initiator comprises benzoyl peroxide; Preferably, the first persulfate initiator includes any one of potassium persulfate, sodium persulfate or ammonium persulfate, or a combination of at least two thereof; Preferably, based on the total mass of the reactive monomer, the first cross-linking agent and the functional monomer being 100%, the mass of the first initiator is 0.1%-10%.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The raw materials for preparing the polymer-based spheres also include a solvent; Preferably, the solvent includes any one of water, anhydrous ethanol, isopropanol, ethyl acetate or n-hexane; Preferably, based on the total weight of the reactive monomer, the first cross-linking agent and the functional monomer as 1 weight part, the weight of the solvent is 5 weight parts to 100 weight parts; Preferably, the raw materials for preparing the polymer-based spheres further include a stabilizer; Preferably, the stabilizer comprises any one or a combination of at least two of polyvinyl pyrrolidone, polyvinyl alcohol, methyl cellulose, ethyl cellulose, hydroxymethyl cellulose, hydroxymethyl propyl cellulose or hydroxyethyl cellulose; Preferably, based on the mass of the solvent being 100%, the mass of the stabilizer is ≤10%; Preferably, the raw materials for preparing the polymer-based spheres further include a first emulsifier; Preferably, the first emulsifier includes any one of polyoxyethylene sorbitan laurate, polyoxyethylene sorbitan stearate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan monopalmitate, sorbitan laurate, polyoxyethylene octylphenol ether, sodium dodecyl sulfate, sodium dodecyl sulfonate or sodium dodecylbenzene sulfonate, or a combination of at least two thereof; Preferably, based on the mass of the solvent being 100%, the mass of the first emulsifier is ≤5%.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The polymerization reaction time is 4-36h; Preferably, the polymerization reaction temperature is 40-90°C; Preferably, the type of polymerization reaction includes any one of emulsion polymerization, soap-free emulsion polymerization, dispersion polymerization, suspension polymerization or microemulsion polymerization; Preferably, the particle size of the polymer-based spheres is 0.1-5 μm.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The reaction in step (2) is carried out in the presence of a first solvent; Preferably, the first solvent comprises water; Preferably, based on 1 part by weight of the polymer-based ball, the mass of the first solvent is 5 parts by weight to 100 parts by weight; Preferably, the metal salt comprises a combination of a divalent metal salt and a multivalent metal salt, and the multivalent metal salt comprises a trivalent metal salt and / or a hexavalent metal salt; Preferably, the divalent metal salt includes any one of a divalent iron salt, a divalent cobalt salt, a divalent nickel salt, a divalent chromium salt or a divalent manganese salt, or a combination of at least two thereof; Preferably, the trivalent metal salt includes any one of a trivalent iron salt, a trivalent cobalt salt, a trivalent nickel salt or a trivalent chromium salt, or a combination of at least two thereof; Preferably, the hexavalent metal salt comprises potassium manganate; Preferably, the divalent metal salt includes any one or a combination of at least two of ferrous chloride, ferrous sulfate, ferrous ammonium sulfate or manganese sulfate; Preferably, the trivalent metal salt comprises any one or a combination of at least two of ferric chloride, ferric sulfate or ammonium ferric sulfate; Preferably, the molar ratio of the multivalent metal salt to the divalent metal salt is 1:(1 / 3-3); Preferably, based on 100% of the mass of the polymer-based ball, the mass of the metal salt is 10%-80%; Preferably, the alkaline solution comprises any one or a combination of at least two of ammonia water, sodium hydroxide solution, potassium hydroxide solution, sodium carbonate solution, potassium carbonate solution or sodium bicarbonate solution; Preferably, the concentration of the alkaline solution is 0.01-17 mol / L; Preferably, based on the mass of the first solvent being 100%, the mass of the alkaline solution is 5%-50%; Preferably, the reaction in step (2) is carried out in the presence of a second emulsifier; Preferably, the second emulsifier includes any one of polyoxyethylene sorbitan laurate, polyoxyethylene sorbitan stearate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan monopalmitate, sorbitan laurate, polyoxyethylene octylphenol ether, sodium dodecyl sulfate, sodium dodecyl sulfonate or sodium dodecylbenzene sulfonate, or a combination of at least two thereof; Preferably, based on 100% of the mass of the polymer-based spheres, the mass of the second emulsifier is 0.01%-20%; Preferably, the reaction temperature in step (2) is 50-80°C; Preferably, the reaction time of step (2) is 1-4h; Preferably, the surfactant comprises any one or a combination of at least two of stearic acid, palmitic acid, lauric acid, oleic acid, 10-undecenoic acid, erucic acid, oleylamine, laurylamine, N,N-dimethyldodecylamine or palmitamine; Preferably, based on 100% of the mass of the metal salt, the mass of the surfactant is 5%-50%; Preferably, the surfactant is used after being diluted with an organic solvent; Preferably, the organic solvent comprises any one or a combination of at least two of anhydrous ethanol, methanol, isopropanol or N,N-dimethylformamide; Preferably, based on 1 part by weight of the surfactant, the mass of the organic solvent is 10 parts by weight to 100 parts by weight; Preferably, the temperature of the physical reaction is 50-80°C; Preferably, the physical reaction time is 1-4h; Preferably, the particle size of the magnetic polymer-based spheres is 0.2-6 μm.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The monomers in step (3) include any one of a second acrylic ester monomer, an unsaturated acid monomer or a styrene monomer, or a combination of at least two thereof; Preferably, the second acrylic acid ester monomer includes any one or a combination of at least two of methyl acrylate, methyl methacrylate, butyl acrylate, butyl methacrylate, glycidyl acrylate or glycidyl methacrylate; Preferably, the unsaturated acid monomer includes any one or a combination of at least two of acrylic acid, methacrylic acid or itaconic acid; Preferably, the styrene monomer includes any one or a combination of at least two of styrene, α-methylstyrene, 4-methylstyrene or sodium 4-styrene sulfonate; Preferably, based on 1 part by weight of the magnetic polymer-based ball, the mass of the monomer is 0.1 parts by weight to 10 parts by weight; Preferably, the second cross-linking agent comprises any one or a combination of at least two of ethylene glycol dimethacrylate, ethylene glycol diacrylate, diethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, 1,4-butanediol dimethacrylate, polyethylene glycol dimethacrylate or divinylbenzene; Preferably, based on 100% of the mass of the monomer, the mass of the second cross-linking agent is 0.1%-10%; Preferably, the raw materials for preparing the magnetic polymer microspheres further include a second initiator; Preferably, the second initiator comprises any one of a second azo initiator, a second peroxide compound initiator or a second persulfate initiator, or a combination of at least two thereof; Preferably, the second azo initiator includes any one of azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate or azobisisobutyramidine hydrochloride, or a combination of at least two thereof; Preferably, the second peroxide compound initiator comprises benzoyl peroxide; Preferably, the second persulfate initiator includes any one of potassium persulfate, sodium persulfate or ammonium persulfate, or a combination of at least two thereof; Preferably, based on the mass of the monomer in step (3) being 100%, the mass of the second initiator is 0.5%-5%; Preferably, the raw materials for preparing the magnetic polymer microspheres further include an emulsifier solution; Preferably, the solute in the emulsifier solution includes any one or a combination of at least two of polyoxyethylene sorbitan laurate, polyoxyethylene sorbitan stearate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan monopalmitate, sorbitan laurate, polyoxyethylene octylphenol ether, sodium dodecyl sulfate, sodium dodecyl sulfonate or sodium dodecylbenzene sulfonate; Preferably, the solvent in the emulsifier solution includes any one of water, ethanol, methanol or isopropanol; Preferably, the solute mass fraction of the emulsifier solution is 0.01%-5%; Preferably, based on 1 part by weight of the monomer in step (3), the mass of the emulsifier solution is 5 parts by weight to 20 parts by weight; Preferably, the reaction in step (3) is carried out in the presence of a second solvent; Preferably, the second solvent comprises water; Preferably, based on 1 part by weight of the magnetic polymer-based ball, the mass of the second solvent is 5 parts by weight to 100 parts by weight; Preferably, the reaction temperature in step (3) is 50-85°C; Preferably, the reaction time in step (3) is 4-24 hours.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The preparation method specifically comprises the following steps: (1) mixing a reactive monomer, a first cross-linking agent, a functional monomer, a solvent, a first initiator, a stabilizer and a first emulsifier and performing a polymerization reaction to obtain a polymer-based ball; Taking the total mass of the reactive monomer, the first cross-linking agent and the functional monomer as 100%, the mass of the reactive monomer is 80%-98.9%, the mass of the first cross-linking agent is 0.1%-10%, the mass of the functional monomer is 1%-10%, and the mass of the first initiator is 0.1%-10%; Based on the total weight of the reactive monomer, the first cross-linking agent and the functional monomer as 1 weight part, the weight of the solvent is 5 weight parts to 100 weight parts; Taking the mass of the solvent as 100%, the mass of the stabilizer is ≤10%, and the mass of the first emulsifier is ≤5%; The polymerization reaction time is 4-36h; The polymerization temperature is 40-90°C; The particle size of the polymer-based spheres is 0.1-5 μm; (2) mixing the polymer-based spheres obtained in step (1) with a first solvent, a metal salt, an alkaline solution, and a second emulsifier to react to obtain a mixture, and adding a surfactant and an organic solvent to the mixture to carry out a physical reaction to obtain magnetic polymer-based spheres; Based on 1 part by weight of the polymer-based ball, the mass of the first solvent is 5 parts by weight to 100 parts by weight; The metal salt comprises a combination of a divalent metal salt and a multivalent metal salt, wherein the multivalent metal salt comprises a trivalent metal salt and / or a hexavalent metal salt; The molar ratio of the polyvalent metal salt to the divalent metal salt is 1:(1 / 3-3); Based on the mass of the polymer-based ball being 100%, the mass of the metal salt is 10%-80%, and the mass of the second emulsifier is 0.01%-20%; Taking the mass of the first solvent as 100%, the mass of the alkaline solution is 5%-50%; The concentration of the alkaline solution is 0.01-17 mol / L; The mass of the surfactant is 5%-50% based on the mass of the metal salt being 100%; Based on 1 part by weight of the surfactant, the mass of the organic solvent is 10 parts by weight to 100 parts by weight; The reaction temperature is 50-80°C; The reaction time is 1-4h; The temperature of the physical reaction is 50-80°C; The physical reaction time is 1-4h; The particle size of the magnetic polymer-based sphere is 0.2-6 μm; (3) mixing the magnetic polymer-based spheres obtained in step (2) with monomers, a second cross-linking agent, a second initiator, an emulsifier solution, and a second solvent, and reacting the mixture to obtain the magnetic polymer microspheres; Based on 1 part by weight of the magnetic polymer-based ball, the mass of the monomer is 0.1 parts by weight to 10 parts by weight, and the mass of the second solvent is 5 parts by weight to 100 parts by weight; Based on the mass of the monomer being 100%, the mass of the second crosslinking agent is 0.1%-10%, and the mass of the second initiator is 0.5%-5%; Based on 1 part by weight of the monomer, the mass of the emulsifier solution is 5 parts by weight to 20 parts by weight; The solute mass fraction of the emulsifier solution is 0.01%-5%; The reaction temperature is 50-85°C; The reaction time is 4-24h.
9. A magnetic polymer microsphere, characterized in that: The magnetic polymer microspheres are prepared by the preparation method according to any one of claims 1 to 8; Preferably, the particle size of the magnetic polymer microspheres is 0.3-8 μm.
10. Use of the magnetic polymer microspheres according to claim 9 in separation, purification or coupling of proteins.
Citation Information
Patent Citations
Sandwich structure magnetic composite micro ball with functional shell layer, its preparing method and use
CN1943560A
Latex of calibrated monodisperse magnetizable microspheres, process of preparation and use of the said latex in chemistry or in biology
US5976426A
Process for producing magnetically responsive polymer particles and application thereof
WO1989004373A1